Comparison of Serum Antibody Titer and Plasma Citrate Using Widal Slide Examination with Different Delay Times - Tiara Wahyu Norbaity Tiara (LPPM Universitas dr. Soebandi, 2024)
Background: The bacteria Salmonella typhi causes typhoid fever, a life-threatening systemic infection. The clinical symptom of typhoid fever that is definitely found is fever. The diagnosis of typhoid fever can be done by performing a Widal examination for supporting examinations. Serum, plasma, and cerebrospinal fluid are samples used for the Widal tube and slide test. The accuracy of the examination must use serum; this is because the Widal examination is very sensitive to the condition of the specimen. Objective: The purpose of this study was to determine the comparison of serum and plasma citrate antibody titers using the Widal slide examination with a delay time of 5 minutes, 10 minutes, and 15 minutes. Method: This research design is an experimental study with quantitative data collection. This study was conducted in June 2024. The sample in this study were patients with typhoid fever aged 5 to 45 years at the Baladhika Husada Hospital Class III Jember with a sample size of 30 respondents using the purposive sampling technique. After the data was collected, the researcher processed the data using SPSS version 26. The data analysis used was the Kruskal-Wallis test, followed by the Duun test. Results: This study obtained an Asymp. Sig. 1,000 α> 0.05 value, then was accepted, meaning that there was no comparison of antibody titers in the results of the Widal slide method examination on serum and citrate plasma, which were delayed for 5 minutes, 10 minutes and 15 minutes and the highest age characteristic results were at the age of 16-25 years and gender in men. Conclusion: There was no comparison of antibody titers in the results of the Widal slide method examination on serum and citrate plasma with a delay time of 5 minutes. 10 minutes and 15 minutes.